2016
DOI: 10.4103/1658-354x.177334
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided injection for plantar fasciitis: A brief review

Abstract: Plantar fasciitis (PF) is a distressing condition experienced by many patients. Although self-limiting, it tends to become a chronic ailment if the precipitating factors are not addressed. One of the modality of treating PF is intra-lesional corticosteroid injection. This was done using palpation technique earlier but nowadays many specialists use ultrasound (US) imaging as a guide to give injection accurately instead of inadvertently damaging the plantar fascia or injecting into surrounding soft tissue, both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
0
1
0
Order By: Relevance
“…[ 18 ] A review article concluded that ultrasound-guided injection had better therapeutic outcomes than palpation-guided injection, and could avoid damaging the plantar fascia or injecting it into surrounding soft tissue. [ 19 ] Ultrasound-guided injection could be done either by in-plane or out-of-plane approach [ Figure 3a and b ].…”
Section: Iagnosismentioning
confidence: 99%
“…[ 18 ] A review article concluded that ultrasound-guided injection had better therapeutic outcomes than palpation-guided injection, and could avoid damaging the plantar fascia or injecting it into surrounding soft tissue. [ 19 ] Ultrasound-guided injection could be done either by in-plane or out-of-plane approach [ Figure 3a and b ].…”
Section: Iagnosismentioning
confidence: 99%
“…It is the most common cause of heel pain, exacerbated by prolonged standing and running. Histologically, there is a predominance of collagen fiber deterioration, fibroblast proliferation, and increased vascularity at the plantar fascia enthesis [ 20 ]. When combined with tibial nerve block, discomfort of the procedure can be alleviated by reducing the signals of the afferent medial and lateral plantar nerves [ 21 ].…”
Section: Plantar Fascia Injection With Nerve Blockmentioning
confidence: 99%